2018
DOI: 10.1371/journal.pone.0201313
|View full text |Cite
|
Sign up to set email alerts
|

Health of undocumented migrants in primary care in Switzerland

Abstract: BackgroundUndocumented migrants endure adverse living conditions while facing barriers to access healthcare. Evidence is lacking regarding their healthcare needs, notably in regards to chronic diseases. Our goal was to investigate health conditions in undocumented migrants attended in primary care setting.MethodsThis study was conducted at the primary care outpatient clinic, Geneva University Hospitals, Switzerland. We retrospectively recorded and coded all medical conditions of a random sample of 731 undocume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 36 publications
2
32
0
1
Order By: Relevance
“…To the best of our knowledge, only one study has previously assessed the prevalence of multimorbidity in UMs. This study of UMs treated in primary care in Switzerland [29] reported a prevalence of multimorbidity of 23% in women and 14% in men, as compared with corresponding values of 12% and 8% in the present study. One possible explanation for these contrasting findings is that our analysis included all individuals with a health card, regardless of whether they availed of public health care.…”
Section: Comparison With Existing Literaturesupporting
confidence: 57%
“…To the best of our knowledge, only one study has previously assessed the prevalence of multimorbidity in UMs. This study of UMs treated in primary care in Switzerland [29] reported a prevalence of multimorbidity of 23% in women and 14% in men, as compared with corresponding values of 12% and 8% in the present study. One possible explanation for these contrasting findings is that our analysis included all individuals with a health card, regardless of whether they availed of public health care.…”
Section: Comparison With Existing Literaturesupporting
confidence: 57%
“…Previous studies showed that undocumented migrants tend to present frequent health problems in the context of adverse living and working conditions [ 3 6 ]. Specifically, undocumented migrants were shown to be at high risk of occupational hazards and chronic physical illnesses [ 7 9 ]. Due to precarious legal and economic conditions, many are forced to perform degrading, physically demanding and low-paid jobs in under-regulated sectors of the labour economy [ 7 , 10 – 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, polymorbidity, often arising at a premature life stage, becomes a challenge among forced migrants in Europe [ 48 ]. The impact of community-acquired infections leading to admission to intensive care units seems much higher in refugees in host countries than in the autochthonous population [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%